Respuesta :

we are given the following expression:

[tex]x^2+12x+25=17[/tex]

First, we will subtract 17 to both sides:

[tex]\begin{gathered} x^2+12x+25-17=17-17 \\ x^2+12x+8=0 \end{gathered}[/tex]

We get an expression of the form:

[tex]ax^2+bx+c=0[/tex]

To complete the square we will add and subtract the following term:

[tex]\frac{b^2}{4a}[/tex]

Replacing the values:

[tex]\frac{12^2}{4(1)}=36[/tex]

Therefore, we will add and subtract 36:

[tex]x^2+12x+36-36+8=0[/tex]

Now we associate the first three terms:

[tex](x^2+12x+36)-36+8=0[/tex]

Now we factor in the associated terms:

[tex](x+6)^2-36+8=0[/tex]

Solving the operations:

[tex](x+6)^2-28=0[/tex]

Now we solve for "x", first by adding 28 to both sides:

[tex](x+6)^2=28[/tex]

Now we take square root to both sides:

[tex](x+6)=\sqrt[]{28}[/tex]

Now we subtract 6 to both sides:

[tex]x=-6\pm\sqrt[]{28}[/tex]

Now we factor 28 as 7*4:

[tex]undefined[/tex]